PERAN PENGUSAHA KERUPUK KETUMBAR DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DI KELURAHAN PALINGKAU BARU KAPUAS MURUNG - Muhammad Amin; Hu’shila Awalia R; Muh. Arief Budiman (JURNAL EKONOMI DAN BISNIS (EKOBIS-DA), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in improving community welfare by creating employment opportunities, increasing household income, and strengthening local economic development. One of the growing MSMEs in Palingkau Baru Village, Kapuas Murung District, is the coriander cracker (kerupuk ketumbar) home industry, which has become an important source of livelihood for local communities. This study aims to analyze the role of coriander cracker entrepreneurs in improving the local economy, identify the socio-economic impacts generated by the business, and examine the supporting factors, constraints, and development strategies for business sustainability. This research employed a qualitative approach using a case study design. Data were collected through observation, in-depth interviews, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing and verification. The findings reveal that the coriander cracker business makes a significant contribution to the local economy by creating employment opportunities, increasing household income, reducing unemployment, and improving family welfare through better access to basic needs, education, housing, and healthcare. In addition to its economic contribution, the business generates a positive multiplier effect by stimulating local economic activities and empowering communities through the utilization of local resources. The sustainability of the business is supported by strong market demand, the availability of local labor, entrepreneurial experience, and community support. However, it also faces several challenges, including limited capital, traditional production technology, inadequate marketing strategies, and dependence on weather conditions during the production process. Therefore, sustainable business development requires product quality improvement, production technology modernization, business management enhancement, digital marketing adoption, business legalization and certification, broader access to financing, and stronger collaboration among entrepreneurs, government institutions, and local communities. This study concludes that the coriander cracker industry serves as an effective instrument for community economic empowerment and sustainable local economic development